Clinical utility of the Glasgow Blatchford Score in patients presenting to the emergency department with upper gastrointestinal bleeding: A retrospective cohort study. (4th February 2021) - Ryan, Kimberley; Malacova, Eva; Appleyard, Mark; Brown, Anthony FT; Song, Lisa; Grimpen, Florian
Abstract: Objective: Upper gastrointestinal bleeding (UGIB) is a common presentation to EDs. Limited Australian data are available. Study aims were to assess mortality and re‐bleeding rates in patients presenting with UGIB as risk‐stratified by the Glasgow Blatchford Score (GBS). Methods: We conducted a retrospective medical chart review of all patients presenting with UGIB to a Brisbane tertiary hospital ED over a 12‐month period. This descriptive study summarised the medical characteristics related to UGIB as risk‐stratified by the GBS. Non‐variceal bleeding was categorised as low‐risk (GBS 0–2) or high‐risk (GBS 3+). Variceal bleeding was not risk stratified. Results: A total of 211 patients presented with UGIB to the ED. The median age was 57 years, 67% were male. Mortality rates at 30 days were: 0% for GBS 0–2, 3% (95% confidence interval [CI] 0–6) for GBS 3+ and 10% (95% CI 0–21) for variceal groups. The overall 30‐day re‐bleeding rate was 4.3% (95% CI 2–7). High‐risk patients accessed endoscopy according to international best practice of less than 24 h (GBS 3+, 23.7 h; variceal bleeding, 7.3 h). Conclusions: Mortality and re‐bleeding outcomes are similar to other international UGIB cohorts. Patients with a low‐risk bleed were appropriately identified and discharged home. Those at higher risk were correctly identified and accessed timely endoscopy. The GBS demonstrated clinical utility in an Australian ED cohort of UGIB bleeding patients. Abstract : Patients with a low‐risk bleed were appropriately identified and discharged home. Those at higher risk were correctly identified and accessed timely endoscopy. Mortality and re‐bleeding outcomes were found to be similar to other international upper gastrointestinal bleeding cohorts.